Network Sharing for Reliable Networks: A Data-Driven Study - Gomes Santos Gonçalves, André Vinícius; Farhang, Arman (My University, 2020)
The next generation of mobile networks will bring an appetite for reliable communication, which enables emerging critical-communication services. In this paper, we present network sharing between operators as a way to provide increased reliability while using the already existing mobile network infrastructure. Our results indicate that network sharing significantly improves network performance during periods of connectivity shortfalls, benefiting the design of reliable networks. Our conclusions are drawn from a real-world dataset of signal quality indicators for three mobile operators in Dublin, Ireland.
IEEE International Conference on Communications
PUBLISHED
Dublin
Keywords: Channel capacity; Signal to noise ratio; Diversity reception; Reliability engineering; Measurement; Radio frequency; Telecommunications